Tuberculosis is a significant problem in children on biologics for rheumatic illnesses: Results from a survey conducted among practicing rheumatologists in India - G Chengappa Kavadichanda; Latika Gupta; Suma Balan (Indian Journal of Rheumatology)
Background: India is endemic for tuberculosis (TB) and the use of immunosuppressants is likely to accentuate the problem. Whilst steroids and conventional disease modifying anti-rheumatic drugs (DMARDs) are believed to increase the risk for tuberculosis, certain biologics such as B cell depleting agents and Interleukin-17 inhibitors are not perceived in the same light. Thus, an attempt was made to capture physicians' perspectives and patterns of biologic DMARDs use in paediatric rheumatology as well as their experience with the occurrence of Tuberculosis in children with rheumatic and musculoskeletal diseases (RMD). Methods: An electronic survey developed on an online cloud-based website (Survey Monkey®) was served to physicians practicing rheumatology in India. Eligible participants (physicians practicing rheumatology) had a week to voluntarily complete the three-minute long questionnaire. While factual set explored observations, opinion set of questions graded perspectives using the Likert scale. Descriptive statistics and figures were obtained from surveymonkey.com. Results: Of the 52 respondents, most of whom were practicing rheumatologists (86.5%), 23 (44.2%) recalled the occurrence of TB after starting biologics. Of these, 13 (25%) encountered this situation in more than one patient. Extra-pulmonary forms of TB were more common (26 of 42, 61.9%), though TB was reported more often while the patient was on biologics than after discontinuing them (n=20 versus 8). Screening strategies varied, with Mantoux, interferon gamma release assay and chest radiographs being used together by most (21, 40%) physicians. Nineteen (52.8%) believed that TB in this setting required longer therapy while 7 (20%) thought adverse drug effects were seen often. Equal number of respondents thought that TB induced diosease flares. Conclusion: TB occurs often in children with RMDs treated with bDMARDs in India. Extra-pulmonary forms are more common and consensus on screening strategies poor. Amongst physicians, there is a perceived risk of prolonged anti-tubercular therapy and adverse drug effects though not of disease flares induced by TB.